Family Planning Counseling During the Covid-19 Pandemic - Riza Fatma Arifa; Dedik Sulistiawan; Muhamad Irfan Munawir Budisantoso (Universitas Aisyah Pringsewu, 2021)
Health services have been directly affected since COVID-19 spread throughout the world, including family planning and counseling services. Various efforts have been made by the government and health providers to continue to carry out family planning (KB) counseling safely. This research was to analyze the behavior of fertile aged couples in accessing family planning counseling services in the Special Region of Yogyakarta. A cross-sectional study using an online survey approach was conducted on a sample of 266 couples of reproductive age who volunteered to participate. Data were analyzed using multiple logistic regression models to identify the correlation between the socio-demographic characteristics of reproductive age couples and the behavior of family planning counseling during the pandemic. The results of this research indicate that the variables most closely related to the behavior of reproductive-age couples in accessing family planning counseling services during the pandemic were the experience of visiting health facilities (AOR = 2.64; 95% CI = 1.42-4.88) and the use of contraception, both modern (AOR = 2.71; 95% CI = 1.34–5.47) and traditional (AOR = 3.67; 95% CI = 1.12–12.02). Based on these findings, it is necessary to strengthen strategies and innovation in the promotion of family planning services to maintain the continuity of contraceptive use by trying to shift offline services to higher quality and safer telehealth services. Abstrak: Layanan kesehatan secara langsung terdampak sejak COVID-19 menyebarluas di seluruh dunia, tak terkecuali layanan keluarga berencana dan konselingnya. Berbagai upaya dilakukan oleh pemerintah maupun provider kesehatan untuk tetap dapat melakukan konseling keluarga berencana (KB) secara aman. Penelitian ini bertujuan untuk menganalisis perilaku pasangan usia subur dalam mengakses layanan konseling KB di Daerah Istimewa Yogyakarta. Studi cross-sectional dengan pendekatan survei daring dilakukan pada sebanyak 266 sampel pasangan usia subur yang sukarela berpartisipasi. Data dianalisis menggunakan model regresi logistik berganda untuk mengidentifikasi hubungan antara karakteristik sosiodemografis pasangan usia subur dengan perilaku konseling KB yang dilakukan selama masa pandemi. Hasil penelitian ini menunjukkan bahwa variabel yang paling erat hubungannya dengan perilaku pasangan usia subur dalam mengakses layanan konseling KB pada masa pandemi adalah pengalaman mengunjungi fasilitas kesehatan (AOR=2,64; 95%CI=1,42–4,88) dan pemakaian kontrasepsi baik modern (AOR=2,71; 95%CI=1,34–5,47) maupun tradisional (AOR=3,67; 95%CI=1,12–12,02). Berdasarkan temuan ini, penguatan strategi dan inovasi promosi layanan KB perlu dilakukan untuk mempertahankan keberlangsungan pemakaian kontrasepsi dengan berupaya menggeser layanan luring menjadi telehealth yang lebih berkualitas dan aman.